1990
DOI: 10.1177/0310057x9001800428
|View full text |Cite
|
Sign up to set email alerts
|

Critical Incidents with Nonrebreathing Valves

Abstract: Nonrebreathing valves have become widely used in conjunction with self-inflating bags and portable ventilators. The ease of use of these devices compared with Mapleson systems and more complex ventilators has led to their use by a wide range of medical, nursing and paramedical staff. There may be an erroneous tendency to regard these systems as foolproof. Four different critical events arising from IPPV with three different models of nonrebreathing valves are described. Casel A 67-year-old male who had remaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…These valves are composed of an inspiratory and an expiratory port and permit either spontaneous or controlled respiration. Patient valves are used for positive pressure ventilation with a BVM or a mechanical ventilator [12]. In most cases, in order to minimize dead space, the valves are situated close to the patient's airway [13, 14].…”
Section: Patient Valve Technical Characteristicsmentioning
confidence: 99%
See 4 more Smart Citations
“…These valves are composed of an inspiratory and an expiratory port and permit either spontaneous or controlled respiration. Patient valves are used for positive pressure ventilation with a BVM or a mechanical ventilator [12]. In most cases, in order to minimize dead space, the valves are situated close to the patient's airway [13, 14].…”
Section: Patient Valve Technical Characteristicsmentioning
confidence: 99%
“…Critical incidents have been documented and a large variety of causes have been identified. Several studies showed some accidents due to faulty one-way valves in BVM and mechanical ventilation [12, 20]. A recent study described a pulmonary barotrauma case due to the “locking” of the Ambu valve in the inspiratory position [20].…”
Section: Bag-valve-mask System Drawbacks and Hazardsmentioning
confidence: 99%
See 3 more Smart Citations